Վանքապատկան եւ եկեղեցապատկան կալվածքների բռնազավթման հարցը Վանի նահանգում (1908-1914 թթ.) - Ավետիս Հարությունյան (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
После младотурецкой революции в 1908 году курдские помещики скрытым путем или насилием сохранили монастырские и церковные поместья армян. Пользуясь протекционизмом младотурок, они не учли истинные жалобы армянских духовных структур. After the coup of the Young Turks in 1908, the Kurdish landlords, in a hidden way or by violence, retained in their hands the monastic and church estates of the Armenians. Taking advantage of the protectionism of the Young Turks, they ignored the factual complaints of the Armenian spiritual structures.
Keywords: History; Armenian Diaspora; Christianity; History of the Armenian Church